Lung tissue damage in the experimental carbon tetrachloride toxicity and protective role of melatonin hormone: A light microscopic and biochemical study - Gülcen, Burak; Karaca, Ömür; Kuş, Murat Abd?lgani; Çolako?lu, Serdar; Ögetürk, Murat; Kuş, Ilter (Duzce University Medical School, 2012)
In this study, it was aimed to investigate the protective effects of melatonin hormone against to carbon tetrachloride (CCl4)-induced toxicity in lung tissue. Twenty-four male Wistar-Albino rats were randomly divided into three equal groups. Rats in group I were used as control. Rats in group II were injected subcutaneously every other day with CCl4. Rats in group III were injected subcutaneously every other day with CCl4 and melatonin. At the end of four weeks of experimental period, all animals were killed by decapitation and their lungs were removed. For biochemical examination, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) enzyme activities and malondialdehyde (MDA) levels were determinated by a spectrophotometer in some of the lung tissue specimens. For light microscopic examination, tissue specimens were embedded in paraffin blocks following routine histological procedures. In lung tissue samples of rats treated with CCl4, SOD and GSH-Px enzyme activities were significantly lower and malondialdehyde (MDA) levels were significantly higher than the control group. Microscopically, interstitial pulmonary hemorrhage, leucocytes with polymorphic nuclei and macrophage infiltration were observed in the lung specimens of rats exposed to CCl4 alone.There is a statistically significant increase in SOD and GSH-Px enzyme activities, and a decrease in MDA levels in rats treated with CCl4 and melatonin. Histopathological changes caused by CCl4 toxicity were not observed in rats treated by melatonin. It is concluded that CCl4 creates oxidative damage in lung tissue and melatonin has protective effects against this CCl4 induced damage. © 2012 Düzce Medical Journal.
Deneysel karbon tetraklorür zehirlenmesinde akci?er doku hasarı ve melatonin hormonunun koruyucu rolü: Işık mikroskobik ve biyokimyasal bir çalışma
Keywords: CCL4; Lung; Oxidative stress; Rat